Role Of Notary/Land Deed Official (PPAT) In Protection Of Sustainable Of Agricultural Land - Ahmad Nur Fauzy al Arif; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Objectives: 1) To determine the role of a Notary / Land Deed Official in the process of sustainable food agriculture land protection. 2) To find out what the barriers and solutions in the implementation of sustainable food agriculture land protection. The data used in this study are primary data, secondary and tertiary data that can menunjamg assessment, which is then analyzed with empirical juridical methods.Based on the results analasis the data concluded that: 1) in the Act No. 41 Year 2009 on Section 37 subsection (e) described the control by way of extension it is related to the role of a Notari / Officer of the Land Deed automatically as a legal consultant and educator law to the people who use the services, this is related to three (3) working on the character's first point explained that the work should reflect the goodwill that realizing the policy in this case related to the protection of agricultural land sustainable food. 2) in the implementation of sustainable food protection of agricultural land is the lack of public knowledge about the rules regarding the protection of farmland this is due to lack of information on the law related to this issue. the increasing number of population also became one of the factors inhibiting the implementation of the protection of agricultural land, the increasing number of residents would increase the demand for homes, it is used as the owners of agricultural land as a business opportunity amid difficult to be farmers at this time, the landowners clicking alihfungsikan land farm into plots of land and housing, and converted into industrial land. Solutions to the government, especially local government; embrace Notary / PPAT in conducting counseling on the protection of agricultural land, as it will not be effective if the government conduct its own extension, construction of flats and industrial areas to be a solution to the need for housing and industrial land. the increasing number of residents would increase the demand for homes, it is used as the owners of agricultural land as a business opportunity amid difficult to be farmers at this time, the land owners alihfungsikan clicking agricultural land into land plots and housing as well as converted into industrial land. Solutions to the government, especially local government; embrace Notary / PPAT in conducting counseling on the protection of agricultural land, as it will not be effective if the government conduct its own extension, construction of flats and industrial areas to be a solution to the need for housing and industrial land. the increasing number of residents would increase the demand for homes, it is used as the owners of agricultural land as a business opportunity amid difficult to be farmers at this time, the land owners alihfungsikan clicking agricultural land into land plots and housing as well as converted into industrial land. Solutions to the government, especially local government; embrace Notary / PPAT in conducting counseling on the protection of agricultural land, as it will not be effective if the government conduct its own extension, construction of flats and industrial areas to be a solution to the need for housing and industrial land. alihfungsikan clicking landowners agricultural land into land plots and housing as well as converted into industrial land. Solutions to the government, especially local government; embrace Notary / PPAT in conducting counseling on the protection of agricultural land, as it will not be effective if the government conduct its own extension, construction of flats and industrial areas to be a solution to the need for housing and industrial land. alihfungsikan clicking landowners agricultural land into land plots and housing as well as converted into industrial land. Solutions to the government, especially local government; embrace Notary / PPAT in conducting counseling on the protection of agricultural land, as it will not be effective if the government conduct its own extension, construction of flats and industrial areas to be a solution to the need for housing and industrial land.